Lack of Adherence of Clinical Isolates of Pseudomonas aeruginosa to Asialo-GM(1) on Epithelial Cells - Schroeder, Torsten H. (American Society for Microbiology, 2001)
Numerous studies have reported that asialo-GM(1), gangliotetraosylceramide, or moieties serve as epithelial cell receptors for Pseudomonas aeruginosa. Usually this interaction is confirmed with antibodies to asialo-GM(1). However, few, if any, of these reports have evaluated the binding of fresh clinical isolates of P. aeruginosa to asialo-GM(1) or the specificity of the antibodies for the asialo-GM(1) antigen. We confirmed that asialo-GM(1) dissolved in dimethyl sulfoxide could be added to the apical membrane of Madin-Darby canine kidney cells growing as a polarized epithelium on Transwell membranes (J. C. Comolli, L. L. Waite, K. E. Mostov, and J. N. Engel, Infect. Immun. 67:3207–3214, 1999) and that such treatment enhanced the binding of P. aeruginosa strain PA103. However, no other P. aeruginosa strain, including eight different clinical isolates, exhibited enhanced binding to asialo-GM(1)-treated cells. Studies with commercially available antibodies to asialo-GM(1) showed that these preparations had high titers of antibody to P. aeruginosa antigens, including whole cells, purified lipopolysaccharide (LPS), and pili. Inhibition studies showed that adsorption of an antiserum to asialo-GM(1) with P. aeruginosa cells could remove the reactivity of antibodies to asialo-GM(1), and adsorption of this serum with asialo-GM(1) removed antibody binding to P. aeruginosa LPS. Antibodies in sera raised to asialo-GM(1) were observed to bind to P. aeruginosa cells by immunoelectron microscopy. Antibodies to asialo-GM(1) inhibited formation of a biofilm by P. aeruginosa in the absence of mammalian cells, indicating a direct inhibition of bacterial cell-cell interactions. These findings demonstrate that asialo-GM(1) is not a major cellular receptor for clinical isolates of P. aeruginosa and that commercially available antibodies raised to this antigen contain high titers of antibody to multiple P. aeruginosa antigens, which do not interfere with the binding of P. aeruginosa to mammalian cells but possibly interfere with the binding of P. aeruginosa cells to each other.